Development of a Data Recording System for COVID-19 Vaccine through the HimproOnline Program, Si Sa Ket Hospital - บุญกัณหา นวรัตน์; หาญเสมอ ประยูร; ชิดชม พงศ์ศิริ; ภูขน เด่นดี (Journal of Health Science of Thailand, 2024)
This study is an action research and a services innovation to develop medical information technology and reduce the work process of Si Sa Ket hospital personnel. The study period was from February 2021 - April 2023. There were steps by designing, and developing the Himpro online program and processing data for COVID-19 vaccine recipients from the database of MOHPROMT, Himpro immunization registration, medical prescriptions and registration of recipirnts of the Himpro online vaccine program. The data were evaluated for accuracy, completeness and duration of data recording. Results of the study found that COVID-19 vaccine services were provided to 238,397 visits from 1 April 2021 - 30 April 2023. Records with Himpro online covered 208,088 visits (87.29%), 100% accuracy, and 100% completeness of the data from 4 databases. The duration of data recording decreased from 7.30 minutes to 2.20 minutes/visit. The program was found to be convenient in providing services to patients outside of the premises. The use of the program was designed to be easy, and saved a lot of time for data entry steps, for recording the data, and for responding to the system for adverse events following immunization and Thailand’s immunization standards in the function of checking personal information from smart card, checking vaccination history with citizen identity number, issuing a consent form for vaccination services, recording vaccine information by reading barcodes, including vaccine type, vial used/shared by person and vaccination provider, ICD10 link with vaccine type, checking the time to monitor adverse events following immunization, issueing a vaccination certificate, and connecting to the MOHPROMT information. The system could be extended to 19 hospitals in Si Sa Ket province that use the Himpro program and continue to develop health promotion and prevention recording service data. It can provide many additional services, such as school immunization, and services for submission of laboratory tests for patients with chronic diseases.